Early and long-term outcome of surgically treated giant internal carotid artery aneurysms—comparison with smaller aneurysms - Szmuda, Tomasz (Springer Vienna, 2011)
BACKGROUND: Internal carotid artery (ICA) is predominant localization of giant intracranial aneurysms (GIAs). The rupture of GIA is supposed to be related to higher risk of poor clinical outcome. Although endovascular techniques are still being developed, they seem to be unsatisfactory in the mean of GIAs. METHODS: Included in the retrospective analysis were 78 giant and 250 smaller surgically treated ICA aneurysms. Exclusion criteria were multiple and blood blister-like aneurysms. Neurological deficit on admission, clinical and radiological presentation, gender, age, segment of ICA, surgical methods, accessory techniques and complications were analyzed. Death rate and short- and long-term outcome of giant aneurysms were compared with smaller aneurysms and risk factors for mortality, unfavorable short- and long-term outcome were determined. RESULTS: There was no difference in general and surgical complications between ICA aneurysm size groups, as well as in occurrence of newly diagnosed neurological deficit after the operation. There were similar mortality rates, proportion of unfavorable outcome, and low health related quality of life for giant and smaller aneurysms. A 12.2% death rate for all ICA aneurysms was achieved. Trapping method as well as Fisher grades 3 and 4 increased mortality risk in the smaller aneurysm group. No significant factors were related to an unfavorable outcome in the ruptured giant aneurysm group. Patients older than 65, Hunt-Hess grades 4 and 5, Fisher grade 4, and newly diagnosed deficit after operation were connected with unfavorable outcome in the ruptured smaller aneurysm group. Newly diagnosed neurological deficit was also an unfavorable outcome risk factor in both giant and smaller ICA unruptured aneurysms. No difference was noted in long-term health-related quality of life between the giant and smaller ICA groups. Higher age and presence of concomitant disease were independent factors affecting quality of life, although obtained data were incomplete. CONCLUSIONS: The study breaks the stereotype of unfavorable giant ICA aneurysms treatment results. Mortality rate, short- and long-term outcome after the operation of giant and smaller ICA aneurysms are similar. Higher age, patients’ condition at admission, and the amount of extravasated blood and trapping method are poor prognostic factors in patients with smaller ICA aneurysm.